P01.167 Impact of retreatment or chemoterapy on survival in patients affected by recurrent glioblastoma: analysis from a single institution. (19th September 2018) - Mazzarella, C; Chiesa, S; Bracci, s; Zinicola, T; Beghella Bartoli, F; Luzi, S; Sabatino, G; Anile, C; Olivi, A; Valentini, V; Balducci, M
Abstract: Background: There is no standard treatment available for recurrent high-grade gliomas. Despite some evidence of improvement in progression-free survival, no significant increase in overall survivor (OS) has been demonstrated with any particular approach. The porpose of this retrospective analysis was to evaluate the impact on OS with different salvage therapies, including no treatment, systemic therapy, or retreatment plus systemic therapy in patients affected by recurrence of Glioblastoma (GBM) to generate new hypotheses for future trial. Material and Methods: Patients (pts) affected by GBM's recurrence and treated with Stupp's schedula, were included in this retrospective analyses. Those who died less a month after progression or with a poor performance status were excluded. Patients were divided into 3 groups: reirradiation plus chemotherapy (group A) chemotherapy alone (group B) no treatment (group C). Overall Survival was calculated using the Kaplan-Meier method and compared between three groups. Results: We retrospectively evaluated files relative to 217 patients with recurrence treated according to Stupp's schedula for GBM from January 2009 to May 2016. Among them, 153 patients were evaluable for this analysis; 64 patients were excluded because they died less than one month after progression or for a poor performance status. Sixty-nine out of 153 patients (45%) belonged to Group C, 63 (41%) to group B, and 21 (14%) to group A. Median follow-up was 48 months in all patients. Median survival time from diagnosis was 18 months for the entire cohort: 14 months for patients of Group C, 28 months for group B, and 30 months for those of group A. Type of treatment at recurrence time proved to significantly impact on OS (p=0.0001). Conclusion: Patients who received no salvage treatment had poorer survival than those who received chemotherapy alone or in combination with radiotherapy. Reirradiation plus chemotherapy seems to favor highest survival. Further investigations are needed to define the optimal choice of therapy, and in particular the role of reirradiation patients with recurrent GBM.